Determinan stunting pada bayi usia 0 – 24 bulan di Kabupaten Pidie: Studi kasus-kontrol - Iin Fitraniar; Faisal Abdurahman; Asnawi Abdullah; Maidar Maidar; Fahmi Ichwansyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
The causes of stunting in toddlers include home environment and maternal factors. Maternal factors include pre-pregnancy nutrition, lack of maternal height, infection during pregnancy, teenage pregnancy, premature birth, short birth spacing, hypertension, maternal mental health, and late initiation of early breastfeeding. The study aimed to determine the association of teenage pregnancy and several other determinants with the incidence of stunting. The research design, namely Case-control, was carried out in 10 health center working areas in Pidie Regency in 2020. The sample comprised 402 infants aged 0 to 24 months, 201 cases and 201 controls. Direct interviews, observations, and anthropometric measures were employed to obtain data. Data processing consists of editing, coding, and tabulation—statistical analysis of the Chi-square test at CI:95%. The results showed that there was an association between teenage pregnancy (p= 0,000), maternal BMI (p= 0,006), premature labor (p= 0,024), maternal education (p= 0,011), income (p= 0,004) with the incidence of stunting. In contrast, there was no association between ANC (p= 0,920), CED (p= 0,303), hypertension (p= 0,96), and maternal occupation (p= 0,119) with the incidence of stunting in toddlers. In conclusion, the determinants of stunting among children under five years old in Pidie Regency are teenage pregnancy, maternal BMI, premature labor, maternal education, and income.Keywords: